Traditional Vernacular Buildings, Architectural Heritage and Sustainability - Almantas Samalavičius; Dalia Traškinaitė (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
The article is focused on vernacular dwellings in different parts of Europe: southern Italy and Lithuania that have their own traditions. The authors note that the attitude towards traditional vernacular architecture has largely changed due to ongoing research in this domail. Nevertheless, despite persistent continuity of traditional architecture, vernacular architecture was affected by the rise and development of modernist ideology that neglected the realm of tradition. The authors discuss some tyoes of vernacular buildings and their relation to local landscape, especially focusing on the traditional vernacular dwelling of Kuršių nerija (coastal regionbordering with Curonian spit and the Baltic Sea. This region was originally an area of fishermen villages and though some of the settlements ceasedf to exist there are a number of vernacula houses that belong to architectural heritage. The issues of dwellings, authenticity, survival and protection as well as some ambiguous issues of sustainability of traditional dwellings arer discussed. The authors conclude by suggesting that multiple assesment perspective should be employed while dealign with vernacular buildings suggesting that buildings of this type can perform functions extending the tourist consumption.